Conservation, restoration and biodiversity of Palaearctic grasslands – Editorial to the 6th EDGG special issue in Hacquetia - Valkó, Orsolya; Labadessa, Rocco; Venn, Stephen (Hacquetia, 2021)
This special issue is a collection of articles about the conservation, restoration and biodiversity of Palaearctic grasslands and was initiated by the Eurasian Dry Grassland Group at the 15th Eurasian Dry Grassland Conference (EDGC), held at Graz, Austria in 2019. The papers in this special issue cover a range of grassland habitats from montane dry grasslands to lowland sandy grasslands, feathergrass steppes and meadow steppes, and focus on the biodiversity values, conservation issues and restoration prospects of Palaearctic grasslands. We hope that the articles in this special issue will contribute to a better understanding of the ecology of grasslands and support their more effective conservation.